Meningkatkan Kemampuan Membaca dengan Metode VATK (Visual, Audio, Taktil, Kinestetik) pada Anak Kesulitan Membaca di Sekolah Dasar - Zuhroh, Luthfiatus; Nugrahani, Rizka Fibria (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Early reading skills are basic skills that children need to have to understand various knowledge. In the learning process that plays an important role is the learning method, the application of the VAKT Method is one method that can be used to improve early reading skills in early grade elementary school students. This study aims to determine the effectiveness of the VAKT method on improving early reading skills in children with reading difficulties in elementary schools. The subjects of this study were 6 students in elementary school. This study used a quasi-experimental design. The sample of this study amounted to 6 people. The treatment given to the subject is the application of the VAKT method. Data analysis methods used with nonparametric techniques (Wilcoxon). The results showed that the application of the VAKT method can improve reading skills in children with reading difficulties in elementary schools, increase initial reading skills in students who have difficulty reading, obtained a Z value of -2.214. The significance value obtains a value of 0.027. judging from the significance value of 0.027<0.05, it means that there is an increase in reading ability with the VATK method (Visual, Audio, Tactile, Kinesthetic) in children with reading difficulties in elementary school